What is the Right Tone? Applying Cialdini’s Persuasion Approaches in Musical Instrument (Revista Interdisciplinar de Marketing, 2020)
The musical instruments market has shown steady growth in recent years. However, few studies have investigated it in Brazil. The present research aims to broaden the understanding of the dynamics of this market in Sao Paulo, focusing on the salesforce in brick and mortar retail stores. The goal is to identify and describe the main selling approaches used by sellers to influence the purchase decisions of consumers. To achieve the goal, we opted for the use of structured interviews, which were conducted with twelve vendors in eight stores in a region specialized in this kind of commerce. The content of the interviews was analyzed qualitatively. To further understand the persuasion approaches, we applied a validated scale (SOCO) to our interviewees. The main findings of the study showed that most vendors use an approach related to tactics of attraction, followed by illusion tactics and, finally, by the approach related to pressure tactics. Such verification leads to the conclusion that sellers tend to adopt sales strategies focused on the consumer. The analysis of the the quantitative data collected by means of the SOCO scale – Sales Orientation-Consumer Orientation – corroborates this conclusion, pointing out that the sellers have high consumer orientation.